2018
DOI: 10.3390/rs10020262
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Leaf Age on Canopy Spectral Signature Variation in Evergreen Chinese Fir Forests

Abstract: Significant gaps exist in our knowledge of the impact of leaf aging on canopy signal variability, which limits our understanding of vegetation status based on remotely sensed data. To understand the effects of leaf aging at the leaf and canopy scales, a combination of field, remote-sensing and physical modeling techniques was adopted to assess the canopy spectral signals of evergreen Cunninghamia forests. We observed an approximately 10% increase in Near-Infrared (NIR) reflectance for new leaves and a 35% incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…This further indicated that photosynthetic pigment content alone provided a somewhat limited indication of stressed trees. At both of the study sites, almost all trees exhibited the usual accumulation of chlorophyll and carotenoids in older needles in comparison with the first year needles (Table 4) [22,85,[87][88][89][90].…”
Section: Photosynthetic Pigmentsmentioning
confidence: 97%
“…This further indicated that photosynthetic pigment content alone provided a somewhat limited indication of stressed trees. At both of the study sites, almost all trees exhibited the usual accumulation of chlorophyll and carotenoids in older needles in comparison with the first year needles (Table 4) [22,85,[87][88][89][90].…”
Section: Photosynthetic Pigmentsmentioning
confidence: 97%
“…At both study sites, almost all trees exhibited the usual accumulation of chlorophyll and carotenoids in older needles in comparison with the 1 st year needles (Apendix A: Figure A1) [22,82,84]. Similarly as for needle biophysical traits, their optical properties are also influenced by needle age [85][86][87] in the following manner: for reflectance in Green and NIR (particularly 750-1000 nm) there is a decrease with needle age [46,86].…”
Section: Discussionmentioning
confidence: 98%
“…With an increasing tree age, a decline in foliage photosynthesis occurs [ 15 ]. In the case of conifer trees, the leaf area index (LAI) is correlated with the age of trees [ 16 ], and needle age has an impact on near-infrared transmittance and reflectance [ 17 , 18 ]. In the case of broad-leaved forests, the influence of forest age on reflectance has also been reported in the near-infrared region [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These relationships should be studied for different tree species, both deciduous and ever-green. In general, this information is valuable to interpret the remote sensing signals, analyze spectral patterns of vegetation and understand the relevant drivers [ 1 , 18 , 48 ]. Also, there is a need to understand how the different stand properties influence the reflectance in terms of estimating forest variables from satellite imagery [ 26 ].…”
Section: Introductionmentioning
confidence: 99%